2004
DOI: 10.1007/bf02256101
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 increases vascular endothelial growth factor and angiogenesis in gastric carcinoma

Abstract: Interleukin-6 (IL-6) is a proinflammatory cytokine associated with the disease status of gastric carcinoma (GC). Vascular endothelial growth factor (VEGF) is a potent tumor angiogenic factor in GC. In this study, we attempted to clarify whether IL-6 can regulate VEGF and angiogenesis in GC. GC samples from 54 surgical specimens were subjected to immunohistochemical examination of IL-6, VEGF, and tumor microvessels, and results showed that IL-6 was positively correlated with VEGF expression and tumor vasculatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(82 citation statements)
references
References 50 publications
5
75
1
1
Order By: Relevance
“…Although previous studies have confirmed that IL-6 is important in both physiological and pathological angiogenesis (Cohen et al, 1996;Mahnke et al, 2000), IL-6 has recently received more attention as a critical cytokine implicated in the angiogenesis of several human cancers, including cervical cancer, basal cell carcinoma, glioma, gastric carcinoma and mesothelioma (Wei et al, 2003;Huang et al, 2004;Jee et al, 2004;Loeffler et al, 2005;Adachi et al, 2006;Saidi et al, 2009). Strikingly, these investigations provide evidence that IL-6 may promote VEGF-induced tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although previous studies have confirmed that IL-6 is important in both physiological and pathological angiogenesis (Cohen et al, 1996;Mahnke et al, 2000), IL-6 has recently received more attention as a critical cytokine implicated in the angiogenesis of several human cancers, including cervical cancer, basal cell carcinoma, glioma, gastric carcinoma and mesothelioma (Wei et al, 2003;Huang et al, 2004;Jee et al, 2004;Loeffler et al, 2005;Adachi et al, 2006;Saidi et al, 2009). Strikingly, these investigations provide evidence that IL-6 may promote VEGF-induced tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…IL-6 is known to regulate VEGF through STAT3 pathway in many cancers and thereby promotes angiogenesis (Wei et al, 2003;Huang et al, 2004;Jee et al, 2004;Saidi et al, 2009). We further examined whether silencing of IL-6 or its downstream target STAT3 in vector or ILK-overexpressing cells could affect VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial cells form the connective and complete tube-like structures with branches when cultured in the appropriate media. The number of tubes was quantified in six different fields for each culture (24). Quantification of tube formation was shown as relative to the control.…”
Section: In Vitro Tube Formation Assaymentioning
confidence: 99%
“…These molecules include interleukin 6 (IL-6) as well as its soluble receptor (sIL-6R) and urokinase-type plasminogen system members. IL-6 stimulates cell proliferation (5) and increases angiogenesis and invasion in tumor cells (6,7). The soluble form of the membrane IL-6 receptor (mIL-6R) binds the cytokine, and their complex is capable of activating the transmembrane protein, gp130, which promotes signal transduction in cells that do not express mIL-6R (IL-6 trans-signaling) (8).…”
Section: Introductionmentioning
confidence: 99%